The Assessment of IL-4 and IgG1 Levels in Patients with Rheumatoid Arthritis and Periodontitis: A Serological Study in Hilla City, Iraq - Mustafa Ibrahim Al Amery; Huda Abbas Mohammed; Zeyad Nazar Majeed (Medical Journal of Babylon)
Background:Periodontal disease, which has a complex etiology, is prevalent and influenced by several factors, including microorganism invasion, host health, and external environmental factors, contributing to its development. It is unknown whether rheumatoid arthritis (RA) and periodontitis are related. Objectives:The current study aims to assess the relationship between periodontitis and RA by measuring the concentrations of interleukin 4 (IL-4) and immunoglobulin G1 (IgG1) in patients’ serum and quantifying Porphyromonas gingivalis in subgingival plaque samples. Materials and Methods:The study comprised patients with periodontitis, RA, and healthy controls. The levels of IL-4 and IgG1 in the serum samples were measured using an enzyme-linked immunosorbent assay. The identification of subgingival plaque bacteria is made by using the polymerase chain reaction technique. Results:The results showed the levels of IgG1 were high in healthy people compared to those with periodontitis and those with periodontitis and arthritis, where the levels in healthy people were 2.3 ± 0.28, 2.06 ± 0.55, 2.05 ± 2.34, 1.82 ± 0.77 in the age groups 41:50, 20:30, 51:60, 31:40, respectively. It was found that there are significant differences between the values of IgG1 and IL-4 in patients with periodontitis at P ≤ 0.05 which is considered a differential sign. Conclusion:The concentrations of IL-4 and IgG1 are decreased in patients (periodontitis and periodontitis with rheumatoid arthritis) compared to their concentrations in healthy people. Thus, we indicate IL-4 was related to reducing the severity of periodontitis disease and RA.